Prevention of hepatic steatosis and hepatic insulin resistance by knockdown of cAMP response element-binding protein - Erion, Derek M; Ignatova, Irena D; Yonemitsu, Shin; Nagai, Yoshio; Chatterjee, Paula; Weismann, Dirk; Hsiao, Jennifer J; Zhang, Dongyan; Iwasaki, Takanori; Stark, Romana; Flannery, Clare; Kahn, Mario; et al. (Cell metabolism, 2009)
In patients with poorly controlled type 2 diabetes mellitus (T2DM), hepatic insulin resistance and increased gluconeogenesis contribute to fasting and postprandial hyperglycemia. Since cAMP response element-binding protein (CREB) is a key regulator of gluconeogenic gene expression, we hypothesized that decreasing hepatic CREB expression would reduce fasting hyperglycemia in rodent models of T2DM. In order to test this hypothesis, we used a CREB-specific antisense oligonucleotide (ASO) to knock down CREB expression in liver. CREB ASO treatment dramatically reduced fasting plasma glucose concentrations in ZDF rats, ob/ob mice, and an STZ-treated, high-fat-fed rat model of T2DM. Surprisingly, CREB ASO treatment also decreased plasma cholesterol and triglyceride concentrations, as well as hepatic triglyceride content, due to decreases in hepatic lipogenesis. These results suggest that CREB is an attractive therapeutic target for correcting both hepatic insulin resistance and dyslipidemia associated with nonalcoholic fatty liver disease (NAFLD) and T2DM.